1992
DOI: 10.1002/etc.5620110203
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and fate of tributyl‐ and triphenyltin compounds in western mediterranean coastal enclosures

Abstract: Tributyltin (TBT) and its degradation products, mono‐ (MBT) and dibutyltin (DBT) have been determined in the dissolved and particulate phases of seawater, sediments, and biota collected in some representative open and enclosed coastal areas of the western Mediterranean Sea. The highest levels were found in sediments and seawater of dry docks and marinas, closely related with boating activity and clearly decreasing according to the distance from the point sources. Triphenyl‐ (TPhT) and diphenyltin (DPhT) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 45 publications
2
35
0
1
Order By: Relevance
“…Still, some mteresting insights can be obtained from comparing our data with those pertaining to other related carnivorous gastropods, particularly if attention is paid to the fact that TPhT is more hydrophobic than TB7 ( m d therefore binds to particulate matter to a larger extent, e.g. Tolosa et al 1992). Thus, Mensink et al 1[1996) found that phenyltin residues were higher than butyltins in Dutch sediment-dwelling whelks (e.g.…”
Section: Imposex Versus Tbt: Differential Sensitivity Of Local Populamentioning
confidence: 93%
“…Still, some mteresting insights can be obtained from comparing our data with those pertaining to other related carnivorous gastropods, particularly if attention is paid to the fact that TPhT is more hydrophobic than TB7 ( m d therefore binds to particulate matter to a larger extent, e.g. Tolosa et al 1992). Thus, Mensink et al 1[1996) found that phenyltin residues were higher than butyltins in Dutch sediment-dwelling whelks (e.g.…”
Section: Imposex Versus Tbt: Differential Sensitivity Of Local Populamentioning
confidence: 93%
“…Aryltin concentrations in Malta waters are comparable to those found in seawater from marinas and drydocks on the Spanish Mediterranean coast [1]. In a more recent study, seawater from these same areas has yielded PhSn 3+ (20-40ngSnL~') as the main aryltin form [22].…”
Section: Phenyltins In Bulk Seawatermentioning
confidence: 50%
“…There is no control over the use of TBTbased antifouling paints in Malta and, using trade statistics, we have estimated that about 3800 L are used annually on small seacraft. The shipbuilding and ship repair industry uses around 4 million L y" 1 . No correlation appears to exist between season and TBT concentration in waters adjacent to the drydocks.…”
Section: Problem Of Co-elution Of Analytesmentioning
confidence: 99%
See 1 more Smart Citation
“…OT contamination has been reported in water, sediment and fish from both freshwater and marine environments in the United States, Europe and Japan (Alzieu et al, 1991;Fent and Hunn., 1991;Kannan et al, 1995a,b,c;Tolosa et al, 1992;Ueno et al, 1999;Borghi and Porte, Correspondence: Margaret M. Whalen, Department of Chemistry, Tennessee State University, 3500 John A. Merritt Blvd., Nashville,TN 37209,Email: mwhalen@tnstate.edu,2002). Environmental contamination resulting from extensive use of OTs has been of great concern due to the potential for deleterious effects on non-target organisms (Kimbrough, 1976;Kannan et al, 1997;Maguire, 2000;Nielsen and Strand, 2002).…”
Section: Introductionmentioning
confidence: 99%